Knowledge Transfer from Local Parent Firms to the Joint-Venture in the South - Maaref, Abdenasser; Djeflat, Abdelkader (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2021)
Today, more North-South Joint-ventures (JVs) are developed mainly to gain greater competitive advantages. Nevertheless, knowledge transfer in North-South JVs did not attract researchers’ interest. Even less known is knowledge transfer between the local parent firm to the JV. This the gap we propose to fill. We will try to identify the determinants of a successful knowledge transfer to that end, we examine four case studies. The findings indicate that there are four main determinants of successful knowledge transfer. The parent firm and the JV need to have them in order to succeed in transferring knowledge.